Public-Private Partnerships: Effective or Damaging to Low-Income Housing Management: A Case Study of Public-Private Partnerships in Affordable Housing Management (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Public-private partnerships are anapproach that has been used in provision of affordable housing in the UnitedStates, as well as in a number of other countries, since the 1980s. In thesepartnerships, private developers, non-profit agencies, and in some casesreligious agencies receive some funds or support from the municipal, state, orfederal government (or all three, in some cases) in order to build or renovateand manage affordable housing. This can be used both for rental housing and asa means of encouraging low-income home ownership. This is also an approach thathas been used in a number of other countries. However, the effectiveness ofpublic-private partnerships in the management of affordable housing is not amatter of uncontroversial agreement, and in fact has been challenged by anumber of different research studies. By focusing research on a single citythat has used public-private partnerships in managing affordable housing, theresearch proposed will attempt to identify specific issues within thepublic-private partnership and gauge its effectiveness in this city.